ON ASPECTS OF UPDRAFTS IN .LOCAL SEVERE STORMS: A CONTROL THEORETIC APPROACH - DHAR , P. K.; SINHA, D. K. (MAUSAM, 1994)
In th is pa per. an <e ltO li pt is mad e to app ly a co ntrol theo retical app roach 10 study 1M optimum d istrib ut ion of .vcrM,(' thermal b4 10}mh.-Y (th ermal enere)-). requi red for attainment of maximum ¥mal velocity in ftu" llr~lr.afl . llli, dr,·f'1n ('lnu."nl. hmikall)' 8 transport P"~U. is Uln..titionn.l by the constraint. pullin, Slipul.tion on ,tu-'"",,1h uf .il' "("raae powrr iC'nt'facN b ) ' therm al boo)...,,,")' durilll the lime of cperatloe. The vaJkle lion h as bun soullin Oil the lin~ f ~!'IsJer ."'... or U !'lin~ data. nUl .....tloll)" divorced frum realil)',